Respostas

  • Usuário do Brainly
2014-08-31T14:47:37-03:00
Olá, Amanda !

Como a_1, a_2, \dots, a_{100} é uma PA, temos

a_2-a_1=a_3-a_2=\dots=a_{100}-a_{99}=r.

a_n=a_1+(n-1)r

Note que,

a_2=a_1+r, a_3=a_1+2r e assim sucessivamente, até a_{100}=a_1+99r.

Assim,

a_1-a_{100}=a_1-(a_1+99r)=-99r.

a_2-a_{99}=(a_1+r)-(a_1+98r)=-97r.

a_3-a_{98}=(a_1+2r)-(a_1+97r)=-95r

\dots

a_{49}-a_{52}=(a_1+48r)-(a_1+51r)=-3r

a_{50}-a_{51}=(a_1+49r)-(a_1+50r)=-r

Veja que:

(a_2-a_{99})-(a_1-a_{100})=-97r-(-99r)=2r

(a_3-a_{98})-(a_2-a_{99})=-95r-(-97r)=2r

\dots

(a_{50}-a_{51})-(a_{49}-a_{52})=-r-(-3r)=2r.

Deste modo,

(a_2-a_{99})-(a_1-a_{100})=(a_3-a_{98})-(a_2-a_{99})=\dots=(a_{50}-a_{51})-(a_{49}-a_{52})=2r.

Logo, (a_1-a_{100}),(a_2-a_{99}),\dots,(a_{50}-a_{51}) é uma PA e sua razão, R, é igual a:

R=(a_2-a_{99})-(a_1-a_{100})=-97r-(-99r)=2r
2 5 2